The Effect Of Plyometric Training On Improving Smash Ability In Volleyball Athletes: Meta-Analysis Study - Anggraini , Della Berliana Aprilia; Hariadi, Imam; Hanief, Yulingga Nanda (Jurnal Pendidikan Jasmani (JPJ), 2023)
This study aims to determine the effect of several plyometric exercises on improving smash skills in volleyball. Many studies have conducted this research in the field of sports. Various kinds of studies explain that plyometric training has a very positive effect on improving volleyball smash abilities, but the results of the data presented tend to be different, with this it is necessary to re-analyze the data in order to provide comprehensive information about plyometric training on improving volleyball smash abilities. The meta-analysis method used in this study was assisted by Jeffreys's Amazing Statistics Program (JSAP) software version 0.16.0.0 by collecting data from research results that already exist in databases such as Google Scholar. Literature search from Google Scholar using the keywords: “plyometric” OR “plyometric” AND “smash” with a range of 2010-2022. The sampling technique used in the search for articles is fulltext articles and article research is carried out in Indonesia. The results of the search with these keywords found a population of 979 articles and 11 samples used, then this data will be retrieved according to the inclusion and exclusion that have been determined. The results of this study indicate that the RE model was identified as 1.15 from the results of studies that have been analyzed and there is no publication bias, therefore it can be concluded that plyometric training has a high effect on volleyball smash ability.